Peningkatan Keterampilan Membaca Teks Arab Gundul melalui Aktifitas Membaca Intensif Berbasis Gramatikal : Studi Kasus Mahasiswa Bahasa dan Sastra Arab IAIN STS Jambi - Sri Sudiarti (FENOMENA, 2015)
The objective of this study was to describe: 1) How to teach reading Arabic non syakal through grammatical-based reading activity, 2) The improvement of reading skill of Arabic non syakal through grammatical-based reading activity, and 3) The students’ respond to the teaching of reading of Arabic non syakal. This is a classroom action research. The data was collected by distributing questionnaires and conducting a test to students. The data analyzed by using Miles and Hubberman model. The result of this study found : 1) The students’ reading ability of Arabic non syakal improved after the implementation of grammatical-based reading activity, 2) The students motivated and enjoyed learning Arabic reading non syakal through grammatical-based reading activity, 3) The students stated that the textbook is applicable to help them understand Arabic text non syakal, and 4) There was a positive respond of the students after learning Arabic reading non syakal through grammatical-based reading activity.